Analisis Morfo-Anatomi Daun Sirih dari Famili Piperaceae dan Araceae di Kampung Warung Peuteuy, Kecamatan Cicalengka - Moch. Naufal Ramdhani; Awaludin Firdaus; Hanifah Flora Reine; Ateng Supriyatna (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
. This research was conducted to identify differences in morphology and anatomy of betel leaves from the Piperaceae family and the Araceae family. In Warung Peuteuy Village, Cicalengka District, there are several species of betel leaves from the Piperaceaae and Araceae families which have different anatomical characteristics and leaf shapes. This study aims to determine the differences in terms of anatomical and morphological characteristics of betel leaves from the Piperacea family and the Araceae family. This research is descriptive in nature by explaining and describing the morphological and anatomical characters of 3 types of betel plants, namely green betel, red betel and ivy betel. Variations in the morphology of betel leaves from the Piperaceae family and the Araceae family can be observed from leaf type, leaf width, leaf length, leaf shape, leaf color, leaf edge, leaf tip, leaf base, leaf veins, petiole color, petiole length, surface, phyllotaxis. Variations in the anatomy of betel leaves from the Piperaceae family and the Araceae family can be observed from variations in the shape of ergastic objects, variations in the number of epidermis layers, number of hypodermis layers, number of palisade parenchyma layers, number of sponge parenchyma layers.